Pengaruh Inflasi Dan Jumlah Penduduk Terhadap Pendapatan Asli Daerah Di Kabupaten Gowa - Fina Octafiani; Asriati, Asriati; Arniati, Arniati (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to examine the effect of inflation and population on Regional Original Revenue (PAD) in Gowa Regency. The research employs a quantitative approach using multiple linear regression analysis and secondary data from 2014 to 2023. The data collection technique used in this study is documentation, by collecting secondary data from official institutions such as the Central Statistics Agency (BPS) and the Regional Financial Agency. The data includes historical records of inflation, population, and regional original revenue in Gowa Regency for the period 2014–2023. The results show that inflation has a positive but not significant effect on PAD, indicating that fluctuations in inflation during the research period did not have a strong enough impact on local revenue. Population also has a positive but not significant effect; although the population increased, low tax compliance likely hindered the optimal growth of PAD.